1992
DOI: 10.1084/jem.175.2.567
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi trans-sialidase and neuraminidase activities can be mediated by the same enzymes.

Abstract: SummaryTrans-sialidase and neuraminidase activities have been detected on the surface membrane of trypomastigotes of Trypanosoma cruzi, and both have been implicated in the parasite's invasion of host cells. We show here that these enzymes are structurally related. They are recognized by two independently derived monoclonal antibodies, are anchored to the membrane by glycosylphosphatidylinositol, copurify by ion exchange, molecular sieving, and hydrophobic chromatography, have maximal activities between pH 6.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
95
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 29 publications
2
95
0
2
Order By: Relevance
“…Our analysis also detected more hits for Group I in the YuYu EVs, which correspond to the proteins containing TS activity, in agreement with our Western blot analysis, which used an antibody to recognize the carboxy-terminal domain of the TS repeats, also denominated shed acute phase antigen (SAPA) [23]. The TS enzymes are known to be released by trypomastigotes and influence the host infectivity [12,44,45] and to stimulate the production of IL-6 in intestinal microvascular endothelial cells and peripheral blood mononuclear cells [46].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our analysis also detected more hits for Group I in the YuYu EVs, which correspond to the proteins containing TS activity, in agreement with our Western blot analysis, which used an antibody to recognize the carboxy-terminal domain of the TS repeats, also denominated shed acute phase antigen (SAPA) [23]. The TS enzymes are known to be released by trypomastigotes and influence the host infectivity [12,44,45] and to stimulate the production of IL-6 in intestinal microvascular endothelial cells and peripheral blood mononuclear cells [46].…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, we detected the presence of the group II more abundantly in the Y-EVs, which correspond to the 85 kDa family of glycoproteins involved in the parasite interaction with host cells. Those proteins harbour the typical FLY sequence and two sialidase domains [4,5,23,42] and monoclonal antibodies against one set of these proteins, called Tc85, partially inhibits the host’s cell invasion by the parasite [43]. …”
Section: Discussionmentioning
confidence: 99%
“…In trypomastigote forms found in the vertebrate host, TS is formed by multimeric aggregates with molecular mass ³400 kDa (15,16), that upon denaturation migrates as multiple bands ranging from 160 to 220 kDa in SDS-PAGE (13,17). Trypomastigote TS has essentially 2 different domains.…”
Section: Structure Of the Trans-sialidasementioning
confidence: 99%
“…Many of these proteins have been implicated in a number of biological processes important for T. cruzi interaction with host cells and extra-cellular matrix proteins (6)(7)(8)(9)(10)(11). One group of these proteins are enzymes denominated transsialidase (TS) that catalyze the transfer of sialic acid to ß-galactosyl residues of mucinlike glycoproteins that are present on the surface of T. cruzi trypomastigotes and epimastigotes (12,13).…”
Section: Structure Of the Trans-sialidasementioning
confidence: 99%
“…Parodi et al (1992) demonstrated that the activities of neuraminidase and trans-sialidase co-precipitated with the same antibody, and Schenkman et al (1992) unequivocally showed that both activities belonged to the same enzyme. Finally, when the deduced amino acid sequence from TCNA was compared with the sequence of SAPA there was 84% homology corresponding to 93% of sequence identity in the nucleotide sequence.…”
Section: The Trans-sialidase Superfamilymentioning
confidence: 99%